2017
DOI: 10.1016/j.freeradbiomed.2017.07.025
|View full text |Cite
|
Sign up to set email alerts
|

Peroxyl radical- and photo-oxidation of glucose 6-phosphate dehydrogenase generates cross-links and functional changes via oxidation of tyrosine and tryptophan residues

Abstract: Protein oxidation is a frequent event as a result of the high abundance of proteins in biological samples and the multiple processes that generate oxidants. The reactions that occur are complex and poorly understood, but can generate major structural and functional changes on proteins. Current data indicate that pathophysiological processes and multiple human diseases are associated with the accumulation of damaged proteins. In this study we investigated the mechanisms and consequences of exposure of the key m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 84 publications
1
60
0
Order By: Relevance
“…() emphasised that the reduced maximum UV absorption peak of proteins is mainly ascribed to the oxidative modification of tyrosine and tryptophan residues on protein surfaces. Similar to tryptophan residues, tyrosine is susceptible to oxidation by ROO· (Leinisch et al ., ), and a hydrogen atom‐abstracted reaction occurs at the heteroatom substitute (Zhang et al ., ), thereby producing tyrosyl phenoxyl radical (Jongberg et al ., ). The coupling of two tyrosyl radicals can further generate dityrosine via a covalent bond and consequently enhance intra‐ or inter‐ molecular protein crosslinking (Zhang et al ., 2017b).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…() emphasised that the reduced maximum UV absorption peak of proteins is mainly ascribed to the oxidative modification of tyrosine and tryptophan residues on protein surfaces. Similar to tryptophan residues, tyrosine is susceptible to oxidation by ROO· (Leinisch et al ., ), and a hydrogen atom‐abstracted reaction occurs at the heteroatom substitute (Zhang et al ., ), thereby producing tyrosyl phenoxyl radical (Jongberg et al ., ). The coupling of two tyrosyl radicals can further generate dityrosine via a covalent bond and consequently enhance intra‐ or inter‐ molecular protein crosslinking (Zhang et al ., 2017b).…”
Section: Resultsmentioning
confidence: 99%
“…It is possible therefore that ROOÁ may transfer to the folded regions and directly attack those buried amino acids. Among the aromatic amino acids, tyrosine and tryptophan residues are prone to oxidation by ROOÁ (Leinisch et al, 2017). The oxidation of these buried residues can result in protein unfolding (Zhang et al, 2013).…”
Section: Changes In Surface Hydrophobicitymentioning
confidence: 99%
See 1 more Smart Citation
“…5, 2018 More recently, oxidation of the enzyme glucose 6-phosphate dehydrogenase initiated by peroxyl radicals, or by photo-sensitized Rose Bengal, has been comprehensively compared. 54 This study showed inactivation of the enzyme and the formation of various cross-links between Tyr-Tyr and Trp-Tyr residues, depending on the oxidizing system. The photo-sensitization of Rose Bengal produces 1 O 2 , which led to the formation of Tyr276-Tyr284, Tyr451-Tyr461 and Trp 203-Tyr207 cross-links.…”
mentioning
confidence: 86%
“…Amino acid analysis by UPLC with fluorescence detection. Samples were prepared and subjected to acid hydrolysis using 4 M methanesulfonic acid as previously 29,30 . The resulting amino acid mixtures were subjected to pre-column derivatization using o-phthaldialdehyde and separated by UPLC with eluted materials detected by fluorescence (λ ex 340 nm, λ em 440 nm).…”
Section: Sds Gel Electrophoresis Protein Samples For Sds Gels Were Amentioning
confidence: 99%